Pengaruh Dukungan Teman Sebaya Terhadap Perilaku Bullying di Lingkungan Sekolah SMK Fajar Ciseeng, Jl. Fajar, RT.007/RW003, Kelurahan Babakan, Kecamatan. Ciseeng, Kabupaten Bogor, Jawa Barat 16120 - Susilawati Susilawati; Nabila Najwasara; Nabilah Nabilah; Irfan Rizka Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Abstract. Bullying remains a common social issue in schools, negatively impacting students' psychological and social development, as well as their academic achievement. One social element that plays a crucial role in the emergence or reduction of bullying is peer support. This support includes acceptance by the social group, empathy, emotional support, and positive participation in daily interactions between students. This study aimed to examine how peer support influences bullying behavior in the school environment. We employed quantitative methods with a correlational design. We collected data using a questionnaire that assessed students' perceived peer support and the intensity of their bullying behavior. To analyze the data, we used regression techniques to determine the direction and strength of the relationship between these variables. The findings revealed that peer support significantly influenced bullying behavior; the stronger the support students perceived from peers, the less likely they were to engage in bullying. These results suggest that a supportive peer environment can act as a buffer against bullying in schools. Therefore, schools should design programs that increase solidarity, empathy, and positive support among students as a preventative measure to reduce bullying behavior.. Keywords: Peer support; Bullying behavior; School environment; Social interaction; Students